2015
DOI: 10.1039/c5ra12808k
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature synthesis of mesoporous CuO and its catalytic activity for cyclohexene oxidation

Abstract: CuO nanoleaves with mesoporous structure were formed in aqueous solution of triethylamine at room temperature. The growth process of the CuO nanoleaves in triethylamine solution was investigated by varying reaction time. It is shown that the CuO nanostructures form by a reconstructive transformation from Cu(OH)2, going through a 0 D nanoparticle →1 D nanowire →2 D nanoleaf dimensional transition process. The mechanism for the amine-induced formation of CuO at room temperature was studied by using different ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…The CuO(A 24 h -C 4 h ) powder catalyst exhibits a nearly type IV nitrogen isotherm with a hysteresis loop in the range of 0.6-1.0 relative pressure, characteristic of mesoporous structured CuO nanomaterials. 36,37 Even though the plateau is not so well dened leading to an upswing at relatively high pressure, this could be due to the presence of wider mesopores and narrow macropores. The pore size distribution (PSD) taken from the quantity desorbed shows a slightly wide distribution with a peak at a diameter of about 13-15 nm and a tail aer 50 nm.…”
Section: 28mentioning
confidence: 99%
“…The CuO(A 24 h -C 4 h ) powder catalyst exhibits a nearly type IV nitrogen isotherm with a hysteresis loop in the range of 0.6-1.0 relative pressure, characteristic of mesoporous structured CuO nanomaterials. 36,37 Even though the plateau is not so well dened leading to an upswing at relatively high pressure, this could be due to the presence of wider mesopores and narrow macropores. The pore size distribution (PSD) taken from the quantity desorbed shows a slightly wide distribution with a peak at a diameter of about 13-15 nm and a tail aer 50 nm.…”
Section: 28mentioning
confidence: 99%
“…9 The commonly used catalysts for the oxidation of cyclohexene consists of metals-free or metals incorporated organic catalysts such as organometallic compounds and metal-organic frameworks, bare metal oxides, metal oxide hybrids, supported metal oxides and so on. [10][11][12] Homogeneous catalysts were reported to be more effective for the liquid phase oxidation reactions and highly suitable to investigate the reaction mechanism. However, due to the difficulties associated with their isolation from reaction mixture and high susceptibility to drastic reaction conditions, their recyclability is restricted.…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated the catalytic reactivity of the multimetallic SNPs by using cyclohexene as a model substrate, which is one of the important C6 compounds in the chemical industry [24, 25] . Although many studies of the catalytic oxidation reaction of cyclohexene have been reported especially for the NP catalysts, they have required severe reaction conditions such as high temperature, high pressure, use of strong oxidants, and addition of initiators [26–30] . In this study, using the highly reactive SNP catalysts, we newly investigated this reaction under the very mild condition at low temperature, at atmospheric pressure, with molecular oxygen as a weak oxidant, and without initiators.…”
Section: Figurementioning
confidence: 99%